AGENSI DALAM KESIAPSIAGAAN BENCANA BANJIR BANDANG DAN TANAH LONGSOR DI PERKEBUNAN KALIJOMPO JEMBER - Shodiq, M. Nur; Mulyono, Joko; Handayani, Baiq Lily (Jurnal ENTITAS SOSIOLOGI, 2018)
Indonesia which is rich in natural landscapes such as mountain, valley and numerous rivers possesses the risk of flash flood and landslide as the consequence. The risks increase even more due to equator line crossing Indonesia and nature exploitation by a human. These landscape characteristics, as well as the potential of flash flood and landslide, are also found in Kalijompo Plantation, Jember District. Therefore, alertness toward disasters is needed. This study is conducted to describe and to analyze the agency in alertness toward flash flood and landslide in Kalijompo Plantation, Jember District. This research uses qualitative approach through doing interview, documentation, and observation. Anthony Giddens? agency theory is borrowed as the theoretical approach. After doing interview, documentation, and observation, it is found that alertness by the agency in Kalijompo Plantation toward flash flood and landslide shows the agency in this context acting as facilitator, provocateur, and motivator. Where the agency has rationalization toward its behavior which is categorized as a rational action. Whereas, the agency?s motive in this context is social and economy.  Keywords: Agency, Alertness, Flash Flood, Land Slide